2020
DOI: 10.1534/genetics.120.303051
|View full text |Cite
|
Sign up to set email alerts
|

A ZZ/ZW Sex Chromosome System in Cephalochordate Amphioxus

Abstract: Sex determination is remarkably variable among animals with examples of environmental sex determination, male heterogametic (XX/XY) and female heterogametic (ZZ/ZW) chromosomal sex determination, and other genetic mechanisms. The cephalochordate amphioxus occupies a key phylogenetic position as a basal chordate and outgroup to vertebrates, but its sex determination mechanism is unknown. During the course of generating Nodal mutants with transcription activator-like effector nucleases (TALENs) in amphioxus Bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…S37 ), but do not exhibit sexually differentiated patterns of mapped read coverage. These results together indicated that all three amphioxus species have independently evolved female heterogametic sex chromosomes, and the result of Bf is consistent with a recent genetic study ( 59 ).…”
Section: Resultssupporting
confidence: 91%
“…S37 ), but do not exhibit sexually differentiated patterns of mapped read coverage. These results together indicated that all three amphioxus species have independently evolved female heterogametic sex chromosomes, and the result of Bf is consistent with a recent genetic study ( 59 ).…”
Section: Resultssupporting
confidence: 91%
“…In other groups, such as Lepidoptera or parasitic flatworms from the genus Schistosoma, sex is determined by a ZW system, with ZZ individuals being males and ZW (or Z0) individuals being females. Such a system was also recently reported in the lancelet Branchiostoma floridae [63]. Depending on the clade, sex chromosomes can be highly conserved, as in Lepidoptera where the ZW pair has been conserved for more than 230 Myr [64], or can vary greatly even between sister families, as in Diptera where new sex chromosomes have appeared at least seven times in less than 300 Myr [65].…”
Section: Genetic Sex Determination System (Gsd): Sex Determined At Fertilization 221 Sex Chromosomessupporting
confidence: 63%
“…The sex-determination (SD) mechanisms of amphioxus remain largely enigmatic, with no cytogenetic evidence for the existence of differentiated sex chromosome pair in Bf and Bb ( 19, 47 ). A recent genetic study suggested that Bf has a female heterogametic sex chromosome system (male ZZ, female ZW) ( 48 ). We confirmed this by generating a heterozygous female mutant strain of Pitx with transcription activator-like effector nucleases (TALENs), whose mutant alleles are only carried by their daughters.…”
Section: Resultsmentioning
confidence: 99%